The wall as a symbol of (false) knowledge in the works of Austrian women writers in the second half of the 20th – beginning of the 21st century - Davydzenka, Darja K. (Journal of the Belarusian State University. Philology, 2024)
The wall image in the works of Austrian women writers in the second half of the 20th – beginning of the 21st century: in the novels «The wall» by M. Haushofer and «Malina» by I. Bachmann, as well as in the mini-play «The wall» by E. Jelinek. The symbolic meaning of the wall in each of the works is analysed. The evolution of the image is explored, which can be particularly clearly traced in E. Jelinek’s mini-play. E. Jelinek’s critique and reinterpretation of the work of her predecessors, M. Haushofer and I. Bachmann, within the framework of the problems associated with the search for female identity through authorship, reveals another facet of her work, namely, as a writer as the work of the next generation of authors who continue to search for solutions to the conflicts that have arisen in the field. It is revealed that the image of the wall is not only a meaning-forming link in the above-mentioned works, but also reflects the changes in the perception of the female author in the patriarchal discourse.
Keywords: wall image; personal identity; Austrian literature; literary discourse; intertextuality